2018
DOI: 10.1097/mpg.0000000000002049
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation on Vitamin D Levels in a Cohort of Pediatric Patients With Inflammatory Bowel Disease

Abstract: Inflammation inversely correlates to VDBP concentrations and patients with IBD, despite their deficiency in total 25(OH)D, have normal or even higher levels of free 25(OH)D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 44 publications
2
17
1
Order By: Relevance
“…Serum concentrations of VDBP only have been studied in 1 cohort of children with IBD. This study found that serum VDBP concentrations were lower in children with IBD when compared to healthy controls, but no correlation between serum VDBP and serum 25(OH)D concentrations was found . Although loss of VDBP has been proposed as a cause of decreased 25(OH)D concentrations in dogs with hypoalbuminemia secondary to IBD, we are not aware of any previous study of serum VDBP concentrations in dogs with CIE.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Serum concentrations of VDBP only have been studied in 1 cohort of children with IBD. This study found that serum VDBP concentrations were lower in children with IBD when compared to healthy controls, but no correlation between serum VDBP and serum 25(OH)D concentrations was found . Although loss of VDBP has been proposed as a cause of decreased 25(OH)D concentrations in dogs with hypoalbuminemia secondary to IBD, we are not aware of any previous study of serum VDBP concentrations in dogs with CIE.…”
Section: Discussioncontrasting
confidence: 65%
“…Direct loss of vitamin D has been suggested as a mechanism, but vitamin D metabolites are primarily transported in the circulation bound to vitamin D‐binding protein (VDBP [85%‐90%]), and to a lesser extent albumin (10%‐15%) . Concentrations of VDBP were decreased in a cohort of children with IBD compared to healthy controls, and in another study, serum 25(OH)D concentration was positively correlated with serum albumin concentration in a group of 130 children and young adults with IBD …”
Section: Introductionmentioning
confidence: 99%
“…In particular, total 25OHD, vitamin D binding protein (VDBP) and bioavailable and free 25OHD are thought to be promising potential (supplementary) markers. Recently, Strisciuglio et al [28] published data from a pediatric population with IBD, albeit a relatively small sample, showing that despite low levels of total 25OHD, concentrations of free 25OHD were normal or increased. In addition, whereas a significant direct correlation was identified between free 25OHD and disease activity indices, no similar relationship was found between total 25OHD and serological markers of inflammation (CRP, fecal calprotectin).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors found that VDBP levels were inversely correlated with inflammation in pediatric IBD, and it is speculated that the underlying reasons were reduced liver production and/or intestinal losses [5].…”
Section: Vitamin D Binding Proteinmentioning
confidence: 99%
“…Vitamin D insufficiency (serum 25OHD concentration ≤20 ng/mL) and deficiency (≤15 ng/mL) are frequently found in healthy adults and adolescents, particularly in the northern hemisphere [1]. A higher prevalence of vitamin D insufficiency and deficiency among adults and children with inflammatory bowel disease (IBD) has been reported [2][3][4][5], despite the existence of controversies [6,7]. The evaluation of vitamin D status and skeletal health in pediatric IBD has been recommended, and the promotion of physical activity may be an important measure in enhancing bone mineral density [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%